Ultraviolet-initiated self-repairing double-container waterborne epoxy anticorrosive paint
By using ultraviolet light in anticorrosion coatings, the dual-container water-based epoxy anticorrosion coatings caused by self-healing, using nanotechnology to encapsulate healing agents, the problems of insufficient barrier performance and environmental protection of traditional anticorrosion coatings are solved, and efficient metal self-repair and environmentally friendly anticorrosion effects are achieved. .
Patent Information
- Application Number
- CN202411843462.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-14
- Publication Date
- 2025-02-11
AI Technical Summary
When traditional anticorrosion coatings face metal corrosion, their barrier properties are limited, and commonly used corrosion-inhibiting fillers are harmful to the environment and human health, making it difficult to achieve environmentally friendly and efficient anticorrosion effects.
A dual-container aqueous epoxy anticorrosion coating that triggers self-healing by using ultraviolet light, uses polymer-based healing agent to induce cross-linking reactions to achieve self-healing of metal surfaces by encapsulating polymer-based healing agents in nanotubes and nanoparticles.
During damage, the coating releases aqueous epoxy resin through the rupture of the nanotubes and undergoes cross-linking reaction under ultraviolet light, which significantly improves the anti-corrosion performance and self-healing ability of the metal surface and reduces the impact on the environment and human health.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to a double-container waterborne epoxy anticorrosive coating capable of self-repairing triggered by ultraviolet light. Background Art
[0002] Metal corrosion is ubiquitous and poses a serious threat to engineering equipment, human health and environmental safety. Traditional anti-corrosion methods, such as organic coatings, are convenient and effective, but their barrier properties are limited and they are easily penetrated by corrosive media. To improve the protective effect, toxic corrosion-inhibiting fillers, such as red lead and hexavalent chromium, are often added to organic coatings, but these fillers are harmful to the environment and human health.
[0003] Therefore, environmentally friendly and efficient corrosion inhibitors have become a research hotspot. At the same time, self-healing technology, as an emerging concept, can bionic self-repair cracks on metal surfaces without human intervention, thereby extending the service life of metals. Inhibitors and polymer healing agents are commonly used self-healing materials, but adding them directly to the coating will reduce their self-healing ability.
[0004] To solve this problem, the present invention relates to a technology for encapsulating a polymer-based healing agent in a micro-nano container. The rupture of the nano container can release the healing agent, achieving self-repair of the crack. This technology has great potential in the preparation of anti-corrosion coatings with self-repairing function. Summary of the invention
[0005] A UV-triggered self-healing dual-container waterborne epoxy anticorrosion coating has been developed to improve the anticorrosion performance of metal surfaces while reducing the impact on the environment and human health. The coating combines self-healing technology to provide a new solution for metal corrosion protection.
[0006] The invention studies a UV-induced self-repairing double-container water-based epoxy anticorrosive coating, which mainly comprises the following components by weight: 100 parts of water-based epoxy resin; 40 parts of curing agent; 5-10 parts of double nano-containers; and 1-10 parts of filler.
[0007] As a preferred technical method of the present invention, the water-based epoxy resin is bisphenol A epoxy resin E-51.
[0008] As a preferred technical method of the present invention, the curing agent is one or two of polyamide and diethyltriamine.
[0009] As a preferred technical method of the present invention, the dual nanocontainer uses nanotubes to encapsulate epoxy resin and nanoparticles to encapsulate UV initiators, wherein the nanotubes are one or more of halloysite nanotubes, carbon nanotubes, and polypyrrole nanotubes, the nanoparticles are one or two of mesoporous silica and mesoporous titanium dioxide, and the UV initiator is one or two of triarylsulfonyl hexafluorophosphate and polypropylene glycol.
[0010] As a preferred technical method of the present invention, the preparation method of the dual nano container is as follows:
[0011] S1. First, 5-10 parts of nanotubes were mixed with 10-20 parts of epoxy resin, placed in a vacuum container, and vacuum and ambient pressure were applied alternately. After evacuating to -0.1 MPa and maintaining for 1 hour, the pressure was returned to atmospheric pressure for 10 minutes. The vacuum-normal pressure cycle was repeated 5 times to ensure efficient loading of epoxy resin.
[0012] S2. Disperse 1-5 parts of nanoparticles and 5-10 parts of UV initiator by ultrasonic mixing for 2 h.
[0013] S3. The nanotubes loaded with epoxy resin and the nanoparticles loaded with UV initiator in the inner cavity were collected by centrifugation and washed with deionized water and anhydrous ethanol. The product was placed in a 60 °C oven for 24 h. When the total amount in the formula remained unchanged, the ratio of the two nanocontainers added was kept at 2:1 for nanotubes: nanoparticles.
[0014] As a preferred technical method of the present invention, the filler is a compound of defoamer BYK-022, leveling agent BYK-345 and film-forming aid propylene glycol methyl ether.
[0015] As a preferred technical method of the present invention, the preparation method of the above-mentioned ultraviolet light-induced self-repairing double-container water-based epoxy anti-corrosion coating comprises the following steps:
[0016] S1, mixing water, defoaming agent and double nano-container in the above proportions and then ultrasonically dispersing to obtain a mixed system;
[0017] S2, adding epoxy resin, film-forming aid, leveling agent and curing agent to the mixed system obtained in S1 in sequence, and mechanically stirring at 500 r / min for 30 min to obtain a uniform coating;
[0018] S3. After the evenly dispersed coating is allowed to stand for 1 hour, it is coated on a polished iron plate with a coating applicator to a thickness of about 60 μm. It is then allowed to stand at room temperature to cure, thereby obtaining a UV-induced self-repairing double-container water-based epoxy anti-corrosion coating.
[0019] The beneficial effects of the present invention are:
[0020] The present invention uses nanotubes as a reservoir of waterborne epoxy resin and nanoparticles as a carrier of UV initiator to prepare a dual-container self-repairing waterborne epoxy coating system with the ability to autonomously repair scratches and restore structural functions. During the damage process of the coating, the nanotubes break and the waterborne epoxy resin overflows to fill the damaged part. During this period, the waterborne epoxy resin contacts the UV initiator and begins to undergo a cross-linking reaction under sunlight, eventually healing the cracks. The coating has a strong self-repairing ability, which greatly improves the corrosion resistance of the material. DETAILED DESCRIPTION
[0022] [Example 1]
[0023] For the convenience of comparison, the experimental results are listed in Table 1.
[0024] The present embodiment provides a UV-triggered self-repairing double-container water-based epoxy anti-corrosion coating, which mainly includes the following components by weight: 100 parts of water-based epoxy resin E-51; 40 parts of curing agent polyamide; 6 parts of double nano-containers; and 3 parts of fillers.
[0025] The coating preparation comprises the following steps:
[0026] (1) The dual nanocontainer is prepared by the following steps:
[0027] S1. First, 5 parts of polypyrrole nanotubes were mixed with 10 parts of epoxy resin, placed in a vacuum container, and vacuum and ambient pressure were applied alternately. After evacuating to -0.1 MPa and maintaining for 1 hour, the pressure was returned to atmospheric pressure for 10 minutes. The vacuum-normal pressure cycle was repeated 5 times to ensure efficient loading of epoxy resin.
[0028] S2. Disperse 1 part of mesoporous silica nanoparticles and 5 parts of UV initiator triarylsulfonyl hexafluorophosphate by ultrasonic mixing for 2 hours.
[0029] S3. The nanotubes loaded with epoxy resin and the nanoparticles loaded with UV initiator in the inner cavity were collected by centrifugation and washed with deionized water and anhydrous ethanol. The product was placed in a 60 °C oven for drying for 24 hours. While the total amount in the formula remained unchanged, 6 portions of double nanocontainers were added, in which the ratio of nanotubes to nanoparticles was 2:1.
[0030] (2) The UV-induced self-healing dual-container waterborne epoxy anticorrosion coating is prepared by the following steps:
[0031] S1, mixing 10 parts of water, 1 part of defoaming agent and 6 parts of double nano containers and then ultrasonically dispersing them to obtain a mixed system;
[0032] S2, adding 100 parts of epoxy resin, 1 part of film-forming aid, 1 part of leveling agent and 40 parts of curing agent polyamide to the mixed system obtained in S1 in sequence, and mechanically stirring at 500 r / min for 30 minutes to obtain a uniform coating;
[0033] S3. After the evenly dispersed coating is allowed to stand for 1 hour, it is coated on a polished iron plate with a coating applicator to a thickness of about 60 μm. It is then allowed to stand at room temperature to cure, thereby obtaining a UV-induced self-repairing double-container water-based epoxy anti-corrosion coating.
[0034] [Example 2]
[0035] For the convenience of comparison, the experimental results are listed in Table 1.
[0036] The present embodiment provides a UV-triggered self-repairing double-container water-based epoxy anti-corrosion coating, which mainly includes the following components by weight: 100 parts of water-based epoxy resin E-51; 40 parts of curing agent polyamide; 6 parts of double nano-containers; and 3 parts of fillers.
[0037] The coating preparation comprises the following steps:
[0038] (1) The dual nanocontainer is prepared by the following steps:
[0039] S1. First, 5 parts of polyhaloysite nanotubes were mixed with 10 parts of epoxy resin, placed in a vacuum container, and vacuum and ambient pressure were applied alternately. After evacuating to -0.1 MPa and maintaining for 1 hour, the pressure was returned to atmospheric pressure for 10 minutes. The vacuum-normal pressure cycle was repeated 5 times to ensure efficient loading of epoxy resin.
[0040] S2. Disperse 1 part of mesoporous silica nanoparticles and 5 parts of UV initiator triarylsulfonyl hexafluorophosphate by ultrasonic mixing for 2 hours.
[0041] S3. The nanotubes loaded with epoxy resin and the nanoparticles loaded with UV initiator in the inner cavity were collected by centrifugation and washed with deionized water and anhydrous ethanol. The product was placed in a 60 °C oven for drying for 24 hours. While the total amount in the formula remained unchanged, 6 portions of double nanocontainers were added, in which the ratio of nanotubes to nanoparticles was 2:1.
[0042] (2) The UV-induced self-healing dual-container waterborne epoxy anticorrosion coating is prepared by the following steps:
[0043] S1, mixing 10 parts of water, 1 part of defoaming agent and 6 parts of double nano containers and then ultrasonically dispersing them to obtain a mixed system;
[0044] S2, adding 100 parts of epoxy resin, 1 part of film-forming aid, 1 part of leveling agent and 40 parts of curing agent polyamide to the mixed system obtained in S1 in sequence, and mechanically stirring at 500 r / min for 30 minutes to obtain a uniform coating;
[0045] S3. After the evenly dispersed coating is allowed to stand for 1 hour, it is coated on a polished iron plate with a coating applicator to a thickness of about 60 μm. It is then allowed to stand at room temperature to cure, thereby obtaining a UV-induced self-repairing double-container water-based epoxy anti-corrosion coating.
[0046] [Example 3]
[0047] For the convenience of comparison, the experimental results are listed in Table 1.
[0048] The present embodiment provides a UV-triggered self-repairing double-container water-based epoxy anti-corrosion coating, which mainly includes the following components by weight: 100 parts of water-based epoxy resin E-51; 40 parts of curing agent diethyltriamine; 6 parts of double nano-containers; and 3 parts of fillers.
[0049] The coating preparation comprises the following steps:
[0050] (1) The dual nanocontainer is prepared by the following steps:
[0051] S1. First, 5 parts of carbon nanotubes were mixed with 10 parts of epoxy resin, placed in a vacuum container, and vacuum and ambient pressure were applied alternately. After evacuating to -0.1 MPa and maintaining for 1 hour, the pressure was returned to atmospheric pressure for 10 minutes. The vacuum-normal pressure cycle was repeated 5 times to ensure efficient loading of epoxy resin.
[0052] S2. Disperse 1 part of mesoporous titanium dioxide nanoparticles and 5 parts of UV initiator polypropylene glycol by ultrasonic mixing for 2 hours.
[0053] S3. The nanotubes loaded with epoxy resin and the nanoparticles loaded with UV initiator in the inner cavity were collected by centrifugation and washed with deionized water and anhydrous ethanol. The product was placed in a 60 °C oven for drying for 24 hours. While the total amount in the formula remained unchanged, 6 portions of double nanocontainers were added, in which the ratio of nanotubes to nanoparticles was 2:1.
[0054] (2) The UV-induced self-healing dual-container waterborne epoxy anticorrosion coating is prepared by the following steps:
[0055] S1, mixing 10 parts of water, 1 part of defoaming agent and 6 parts of double nano containers and then ultrasonically dispersing them to obtain a mixed system;
[0056] S2, adding 100 parts of epoxy resin, 1 part of film-forming aid, 1 part of leveling agent and 40 parts of curing agent polyamide to the mixed system obtained in S1 in sequence, and mechanically stirring at 500 r / min for 30 minutes to obtain a uniform coating;
[0057] S3. After the evenly dispersed coating is allowed to stand for 1 hour, it is coated on a polished iron plate with a coating applicator to a thickness of about 60 μm. It is then allowed to stand at room temperature to cure, thereby obtaining a UV-induced self-repairing double-container water-based epoxy anti-corrosion coating.
[0058] [Example 4]
[0059] For the convenience of comparison, the experimental results are listed in Table 1.
[0060] The present embodiment provides a UV-triggered self-repairing double-container water-based epoxy anti-corrosion coating, which mainly includes the following components by weight: 100 parts of water-based epoxy resin E-51; 40 parts of curing agent diethyltriamine; 6 parts of double nano-containers; and 3 parts of fillers.
[0061] The coating preparation comprises the following steps:
[0062] (1) The dual nanocontainer is prepared by the following steps:
[0063] S1. First, 5 parts of polypyrrole nanotubes were mixed with 10 parts of epoxy resin, placed in a vacuum container, and vacuum and ambient pressure were applied alternately. After evacuating to -0.1 MPa and maintaining for 1 hour, the pressure was returned to atmospheric pressure for 10 minutes. The vacuum-normal pressure cycle was repeated 5 times to ensure efficient loading of epoxy resin.
[0064] S2. Disperse 1 part of mesoporous titanium dioxide nanoparticles and 5 parts of UV initiator polypropylene glycol by ultrasonic mixing for 2 hours.
[0065] S3. The nanotubes loaded with epoxy resin and the nanoparticles loaded with UV initiator in the inner cavity were collected by centrifugation and washed with deionized water and anhydrous ethanol. The product was placed in a 60 °C oven for drying for 24 hours. While the total amount in the formula remained unchanged, 6 portions of double nanocontainers were added, in which the ratio of nanotubes to nanoparticles was 2:1.
[0066] (2) The UV-induced self-healing dual-container waterborne epoxy anticorrosion coating is prepared by the following steps:
[0067] S1, mixing 10 parts of water, 1 part of defoaming agent and 6 parts of double nano containers and then ultrasonically dispersing them to obtain a mixed system;
[0068] S2, adding 100 parts of epoxy resin, 1 part of film-forming aid, 1 part of leveling agent and 40 parts of curing agent diethyltriamine to the mixed system obtained in S1 in sequence, and mechanically stirring at 500 r / min for 30 minutes to obtain a uniform coating;
[0069] S3. After the evenly dispersed coating is allowed to stand for 1 hour, it is coated on a polished iron plate with a coating applicator to a thickness of about 60 μm. It is then allowed to stand at room temperature to cure, thereby obtaining a UV-induced self-repairing double-container water-based epoxy anti-corrosion coating.
[0070] [Comparative Example 1]
[0071] The comparative example provides a self-repairing nanocontainer water-based epoxy anti-corrosion coating. Compared with Example 1, the difference is that a single nanocontainer is used. The coating mainly includes the following components by weight: 100 parts of water-based epoxy resin E-51; 40 parts of curing agent polyamide; 6 parts of nanocontainer; and 3 parts of filler.
[0072] The coating preparation comprises the following steps:
[0073] (1) A single nanocontainer is prepared by the following steps:
[0074] S1. First, 5 parts of carbon nanotubes were mixed with 10 parts of epoxy resin, placed in a vacuum container, and vacuum and ambient pressure were applied alternately. After evacuating to -0.1 MPa and maintaining for 1 hour, the pressure was returned to atmospheric pressure for 10 minutes. The vacuum-normal pressure cycle was repeated 5 times to ensure efficient loading of epoxy resin.
[0075] S2. Collect the nanotubes loaded with epoxy resin in the inner cavity by centrifugation, wash with deionized water and anhydrous ethanol, and dry the product in an oven at 60°C for 24 hours.
[0076] (2) The self-healing nanocontainer waterborne epoxy anti-corrosion coating is prepared by the following steps:
[0077] S1, mixing 10 parts of water, 1 part of defoaming agent and 6 parts of single nanocontainers and then ultrasonically dispersing them to obtain a mixed system;
[0078] S2, adding 100 parts of epoxy resin, 1 part of film-forming aid, 1 part of leveling agent and 40 parts of curing agent polyamide to the mixed system obtained in S1 in sequence, and mechanically stirring at 500 r / min for 30 minutes to obtain a uniform coating;
[0079] S3. After the evenly dispersed coating is allowed to stand for 1 hour, it is coated on a polished iron plate with a coating applicator to a thickness of about 60 μm, and then allowed to stand at room temperature to cure, thereby obtaining a self-repairing nanocontainer water-based epoxy anti-corrosion coating.
[0080] As can be seen from Table 1, compared with Comparative Example 1, the UV-triggered self-repairing double-container waterborne epoxy anti-corrosion coatings prepared in Examples 1-4 of the present invention have strong adhesion, all of which are level 1, high hydrophobicity, and contact angle test results are all greater than 153°. At the same time, they have good light absorption behavior and UV shielding ability. Most importantly, they have excellent self-repairing properties, and the scratch repair rate is higher than 85%.
[0081] Table 1 Comparison of coating properties between the embodiment and the comparative example
[0082] Adhesion (grade) Pencil hardness (H) Contact angle (°) Light absorption behavior Scratch repair rate (%) Example 1 1 H 153 Can shield harmful light below 400nm 88.5 Example 2 1 H 156 Can shield harmful light below 400nm 90.1 Example 3 1 H 154 Can shield harmful light below 400nm 85.4 Example 4 1 H 155 Can shield harmful light below 400nm 89.7 Comparative Example 1 0 H 143 Can shield harmful light below 400nm 50.6
[0083] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention; although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A UV-induced self-repairing double-container waterborne epoxy anticorrosion coating, characterized in that: By weight, it mainly includes the following components: Waterborne epoxy resin, 100 parts; Curing agent, 40 parts; Double nano container, 5-10 servings; Filler, 1-10 parts.
2. The UV-induced self-repairing dual-container waterborne epoxy anticorrosion coating according to claim 1, characterized in that: The water-based epoxy resin is bisphenol A epoxy resin E-51.
3. The UV-induced self-repairing dual-container waterborne epoxy anticorrosion coating according to claim 1, characterized in that: The curing agent is one or two of polyamide and diethyltriamine.
4. The UV-induced self-repairing dual-container waterborne epoxy anticorrosive coating according to claim 1, characterized in that: The double nano-container uses nanotubes to encapsulate epoxy resin and nanoparticles to encapsulate UV initiators, wherein the nanotubes are one or more of halloysite nanotubes, carbon nanotubes, and polypyrrole nanotubes, the nanoparticles are one or two of mesoporous silica and mesoporous titanium dioxide, and the UV initiator is one or two of triarylsulfonyl hexafluorophosphate and polypropylene glycol.
5. The UV-induced self-repairing dual-container waterborne epoxy anticorrosion coating according to claim 4, characterized in that: The steps of preparing the dual nano-container are as follows: S1. First, mix 5-10 parts of nanotubes with 10-20 parts of epoxy resin, place them in a vacuum container, alternately apply vacuum and ambient pressure, evacuate to -0.1 MPa and maintain for 1 hour, then return to atmospheric pressure for 10 minutes. Repeat the vacuum-normal pressure cycle 5 times to ensure efficient loading of epoxy resin; S2, dispersing 1-5 parts of nanoparticles and 5-10 parts of UV initiator by ultrasonic mixing for 2 h; S3. The nanotubes loaded with epoxy resin and the nanoparticles loaded with UV initiator in the inner cavity were collected by centrifugation and washed with deionized water and anhydrous ethanol. The product was placed in a 60 °C oven for 24 h. When the total amount in the formula remained unchanged, the ratio of the two nanocontainers added was kept at 2:1 for nanotubes: nanoparticles.
6. The UV-induced self-repairing dual-container waterborne epoxy anticorrosion coating according to claim 1, characterized in that: The filler is a compound of defoamer BYK-022, leveling agent BYK-345 and film-forming aid propylene glycol methyl ether.
7. The UV-induced self-repairing dual-container waterborne epoxy anticorrosive coating according to claim 1, characterized in that: The preparation method thereof comprises the following steps: S1, mixing water, defoaming agent and double nano-container in the above proportions and then ultrasonically dispersing to obtain a mixed system; S2, adding epoxy resin, film-forming aid, leveling agent and curing agent to the mixed system obtained in S1 in sequence, and mechanically stirring at 500 r / min for 30 min to obtain a uniform coating; S3. After the evenly dispersed coating is allowed to stand for 1 hour, it is coated on a polished iron plate with a film applicator to a thickness of about 60 μm. It is then allowed to stand at room temperature to cure, thereby obtaining a UV-induced self-repairing dual-container water-based epoxy anti-corrosion coating.
Citation Information
Patent Citations
Chromium-free waterborne epoxy anticorrosion primer with excellent solvent oil resistant performance
CN102559010A
Self-repairing photocureable coating composition
CN115386285A
Photo-initiation self-repairing microcapsule containing carbon quantum dots and preparation method thereof
CN116212754A